IMPROVING WRITING SKILL OF THE TENTH-GRADE STUDENTS OF SMA NEGERI 7 PALU BY USING CONTEXTUAL TEACHING AND LEARNING APPROACH - Sari, Puspita; Munir, Syahrul; Maf’ulah, Maf’ulah (Tadulako University, 2024)
This study is aimed at proving whether or not Contextual Teaching and Learning Approach can improve students’ writing skill in descriptive text. This study uses a quasi-experimental research design. It involves the tenth-grade students of SMA Negeri 7 Palu. In selecting the sample, the researcher uses a cluster random sampling, and the students selected as the sample were class X7 and X9. The data of this research is quantitative data. In collecting the data, it is collected through the writing test that consisted of pre-test and post-test. The data gathered is analyzed statistically to analyze the difference of students’ score in experimental and control classes. The results of the data indicates that the mean score of the experimental class (62.05) was higher than the mean score of the control class (52.25). By applying a significance level of 0.05, it is found that the t-counted (6.16) was higher than the t-table (1.67). It means that the hypothesis of the research is accepted. Based on the result, it is concluded that the use of Contextual Teaching and Learning Approach (CTL) can improve the students’ skill in writing descriptive text. The implication of the findings to the teaching of writing in the class is that the teacher needs contextual media to make the class more meaningful and real as well as make the students improve their writing.